2021
DOI: 10.1186/s12885-021-09046-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel pyroptosis-related gene signature predicts the prognosis of glioma through immune infiltration

Abstract: Background Glioma is the most common primary intracranial tumour and has a very poor prognosis. Pyroptosis, also known as inflammatory necrosis, is a type of programmed cell death that was discovered in recent years. The expression and role of pyroptosis-related genes in gliomas are still unclear. Methods In this study, we analysed the RNA-seq and clinical information of glioma patients from The Cancer Genome Atlas (TCGA) database and Chinese Gliom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…The AUC (area under the ROC curve) was 0.85, 0.90, and 0.87 for the 1-year, 3-year, and 5-year OS in the training cohort and 0.72, 0.80, and 0.84 in the CGGA cohort, respectively. The ROC curves showed a similar prognostic value of our established prognostic model and the previously established 10-pyroptosis-gene prognostic model [22] and golden standard WHO grading system for predicting OS at 1, 3, and 5 years in TCGA and CGGA cohorts (Figure S5). Moreover, univariate and multifactorial Cox regression analyses revealed that the Riskscore could be used as a valid independent prognostic factor, as well as disease grade, age, IDH mutation status, and 1p19q codeletion status (Figures 4(e) and 4(f)).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The AUC (area under the ROC curve) was 0.85, 0.90, and 0.87 for the 1-year, 3-year, and 5-year OS in the training cohort and 0.72, 0.80, and 0.84 in the CGGA cohort, respectively. The ROC curves showed a similar prognostic value of our established prognostic model and the previously established 10-pyroptosis-gene prognostic model [22] and golden standard WHO grading system for predicting OS at 1, 3, and 5 years in TCGA and CGGA cohorts (Figure S5). Moreover, univariate and multifactorial Cox regression analyses revealed that the Riskscore could be used as a valid independent prognostic factor, as well as disease grade, age, IDH mutation status, and 1p19q codeletion status (Figures 4(e) and 4(f)).…”
Section: Resultssupporting
confidence: 72%
“…Although there have been several studies on prognosis-related pyroptosis genes in glioma [ 22 , 23 ], they have been limited to establishing a prognostic model based on regression analysis while ignoring the correlation between pyroptosis and the tumor immune microenvironment. Moreover, these studies have tended to analyze all pyroptosis-related genes in general, but different gasdermin-mediated pyroptosis pathways are relatively independent from each other, and many genes are involved in other biological functions, such as apoptosis, so each pathway should be explored independently to reflect the situation of pyroptosis in glioma more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we compared the prognostic predictive abilities of 20 different risk signatures of gliomas in TCGA from published articles, including inflammatory response-related gene (IRRG) signature ( Yan et al, 2022 ), DNA damage and repair-related gene (DDRRG) signature ( Li et al, 2022c ), CXCR members signature ( He et al, 2022 ), pyroptosis-related gene signature ( Zhang M. et al, 2021b ; Chao et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ), ECM-related gene (ECMRG) signature ( Li et al, 2022b ), tripartite motif (TRIM) family gene signature ( Xiao et al, 2022 ), antigen presentation machinery (APM) signature ( Chen et al, 2022 ), natural killer cell-related gene (NKRG) signature ( Li C. et al, 2022a ), IL-4-related gene (IL4RG) signature ( Qi et al, 2022 ), hypoxia-related gene (HRG) signature ( Gao et al, 2021 ), S100 family-based signature ( Hu et al, 2021 ), TIME signature ( Zhang C. et al, 2021a ), focal adhesion-related gene (FARG) signature ( Li et al, 2021 ), m6A RNA methylation regulator signature ( Cong et al, 2021 ), HDAC1-related signature ( Fan et al, 2021 ), RNA-binding protein (RBP)-based signature ( Chen et al, 2021a ) and ferroptosis-related gene (FRG) signature ( Chen et al, 2021b ). The results of univariate and multivariate Cox analyses showed that our ARG signature had independent predictive ability ( p < 0.001, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the integrative roles of multiple pyroptosis-related genes are still poorly elucidated. By identifying the role of pyroptosis regulation patterns in TME, we may better understand the anti-tumor immune response and guide the design of more effective immunotherapy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%